Hepatoprotective activity of prunus persica peaches against paracetamol induced hepatotoxicity - Manokaran, S.; Saravanan, V.S.; Bhargavi, Y.; Pandi, P.V. (2011)
epato-toxicity is a common toxicity happening during the treatment of chronic diseases like tuberculosis, diabetics. Prunus persica belongs to Rosaceae is a plant growing in temperate region used as laxative, sedative, anti-cancer and also consist of glycosides, flavonoids, anthocyanins, vitamins. It also possess hepato-protactent property. To prove the activity scientifically the ethanolic extract of Prunus persica was studied against Paracetamol induced Hepatotoxicity in albino rats. The extract when evaluated at the dose of 100mg / kg was found to significantly reduce the elevated levels of serum Lysosomal enzyme SGPT, SGOT, ALP and Bilirubin when compared with standard Silymarin.